ANALISIS PRESEPSI MASYARAKAT : APLIKASI KONSEP BALANCE SCORECARD DI KANTOR BERSAMA SAMSAT WILAYAH PROVINSI MALUKU UTARA - Sidiq, Fazry (Jurnal MS, 2014)
This research discuses about performance measurement of organization by usingÂ Balanced Scorecard as a method that can be applied in a public sector organization. Nowadays, performance measurement in public sector is still more focused on internal business and short term goals (financial). Therefore, measurement of performance using the Balanced Scorecard (financial perspective, customer perspective, internal business perspective and learning and growth perspective) offers a solution for more comprehensive performance measurement and comprehensive in an organization. The object of this research is Samsat Office North Maluku. The research at samsatÂ office conducted by comparing between internal samsat performance andÂ Balanced Scorecard performance of the years 2009-2011. From the results of research using the Balanced Scorecard, the average value forÂ each perspectives of financial, customer, internal business and learning and growth is good enough. So it can be concluded that the performance of the SamsatÂ office North Maluku included in the criteria sufficiently, with some suggestions and improvements that need to be done.